Peranan Sains Kimia Dalam Melaksanakan Maqasid Syariah Semasa Pandemik. - Musa Ahmad; Muhammad Zamir Othman; Syaza Azhari; Siti Nazurah Md Jusoh (USIM Press, 2024)
Vol. 33 No. 3 (2021): ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences